2008
DOI: 10.1105/tpc.108.058818
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis Reveals That C19-GA 2-Oxidation Is a Major Gibberellin Inactivation Pathway inArabidopsis 

Abstract: Bioactive hormone concentrations are regulated both at the level of hormone synthesis and through controlled inactivation. Based on the ubiquitous presence of 2β-hydroxylated gibberellins (GAs), a major inactivating pathway for the plant hormone GA seems to be via GA 2-oxidation. In this study, we used various approaches to determine the role of C19-GA 2-oxidation in regulating GA concentration and GA-responsive plant growth and development. We show that Arabidopsis thaliana has five C19-GA 2-oxidases, transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
262
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(287 citation statements)
references
References 75 publications
(119 reference statements)
14
262
1
3
Order By: Relevance
“…We therefore considered gibberellin degradation to be negligible in the model. We further confirmed this model assumption by analyzing the morphology of ga2ox quintuple mutants (29), in which five of the GA2-oxidases are no longer expressed (including AtGA2ox6). Measurements of the root growth rate, elongation zone length, and cell lengths were similar to those in wild-type plants (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…We therefore considered gibberellin degradation to be negligible in the model. We further confirmed this model assumption by analyzing the morphology of ga2ox quintuple mutants (29), in which five of the GA2-oxidases are no longer expressed (including AtGA2ox6). Measurements of the root growth rate, elongation zone length, and cell lengths were similar to those in wild-type plants (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 51%
“…Gibberellin can also be deactivated by members of GA2-oxidase family; however, transcriptomics data for dissected regions of the root (28) revealed that the GA2-oxidase is not expressed in the elongation zone [with AtGA2ox6, the main GA2-oxidase expressed in Arabidopsis roots (29), being expressed only once the cells leave this zone]. We therefore considered gibberellin degradation to be negligible in the model.…”
Section: Resultsmentioning
confidence: 99%
“…This chemical treatment was confirmed by mutant analysis. To avoid pleiotropic effects, we selected mutants with altered GA levels or DELLA activity that showed relatively limited growth phenotypes under normal conditions: q-ga2ox, a quintuple knockout for five GA 2-oxidases, resulting in higher GA levels (Rieu et al, 2008a); spy-3, a weak loss-of-function allele of the DELLA activator SPY (Jacobsen and Olszewski, 1993;Silverstone et al, 2007); the double DELLA loss-offunction mutant rga-28 gai-2; and ga3ox1-3, in which the major GA 3-oxidase responsible for GA biosynthesis in vegetative tissues is inactive, resulting in Figure 1. A, Levels of the GA biosynthesis gene GA3OX1 and the GA catabolic gene GA2OX6 at 24 h after transfer to mannitol.…”
Section: Dellas Trigger Mitotic Exitmentioning
confidence: 99%
“…The regulation of GA levels occurs at both biosynthesis, through GA 20-oxidases (GA20OX) and GA 3-oxidases (GA3OX), and degradation, which is mainly catalyzed by GA 2-oxidases (GA2OX). All these enzymes occur in small families in Arabidopsis and have tissue-specific expression patterns (Mitchum et al, 2006;Rieu et al, 2008aRieu et al, , 2008b, allowing for a tight temporal and spatial control of GA levels. GA signaling occurs by binding of GA to its receptor, GA INSENSITIVE DWARF1, leading to the formation of a complex with DELLA proteins, transcriptional regulators that inhibit GA responses in the absence of GA.…”
mentioning
confidence: 99%
“…Upon short‐term exposure to mannitol, a gradually increasing number of genes encoding TFs is significantly upregulated, suggesting that a transcriptional cascade initiates the early response to mannitol. Few members of this transcriptional cascade have been studied previously, such as the rapidly induced ETHYLENE RESPONSE FACTOR 6 ( ERF6 ), which activates the expression of GIBBERELLIN2‐OXIDASE6 ( GA2‐OX6 ), a gene encoding a gibberellin‐inactivating enzyme (Rieu et al , 2008; Dubois et al , 2013). Because of the resulting lower levels of gibberellin, DELLA proteins are stabilized, which ensures that cells permanently exit the cell division phase and are pushed to cell differentiation (Claeys et al , 2012).…”
Section: Introductionmentioning
confidence: 99%